TAX REFORM IN THE CONTEXT OF THE UNION: PROPOSALS FOR CSLL AND IRPJ. (REMUNOM, 2025)
This article critically analyzes the Corporate Income Tax (IRPJ) and the Social Contribution on Net Profit (CSLL), federal taxes that are levied on corporate profits in Brazil. Based on bibliographic and documentary research, the study investigates the origin, evolution and main structural problems of these taxes, such as overlapping bases, regulatory complexity and legal uncertainty. Compared to OECD countries, the Brazilian tax system is excessively burdensome and inefficient, harming competitiveness and the business environment. The central proposal of the article is the abolition of the IRPJ and the creation of a tax on dividends and the restructuring of the CSLL under a progressive tax rate model. The proposal aims to promote greater simplicity, tax justice and alignment with international practices, with the adoption of rates compatible with the global average and gradual transition mechanisms. The study concludes that a profound reform is essential to modernize the national tax system, stimulate productive investment and reduce inequalities, in compliance with the constitutional principles of legality, equality and tax capacity.